Les Accords de Cancún face aux enjeux des négociations internationales sur le climat - René Audet; Patrick Bonin (VertigO, 2010)
The sixteenth Conference of the Parties (COP16) of the United Nations Framework Convention on Climate Change ended on December 11, 2010, on a positive note, as the Cancún Accords were adopted. In order to evaluate the results of COP16, this paper will take on the double task of examining the main issues at stake in the climate negotiations, and of considering the Cancún Accords in light of those issues. The issues are : the future of the multilateral process, the problem of climate injustice, and the uncertainty regarding the legal architecture of the forthcoming climate treaty. This analysis of the Cancún Accords reveals a paradox that the next COP will have to confront at the end of 2011.